The Coping Mechanisms of First-Year Students in the Online Classes - M. Cortes, Venus; Elaine Perez, Lourdes; D. McCarthy, Joanna Ophel; R. Rumol, BM Jade; L. Tulod, Febe Kaye (International Journal of Humanities and Education Development (IJHED), 2022)
The study aimed to determine the coping mechanisms of first-year college students taking Bachelor of Special Needs Education in a state university in the online class setting. It utilized Colaizzi’s (1978) descriptive phenomenological method which followed his seven-step method. Three emergent themes were revealed (1) coping mechanisms, (2) adjustment of 1st-year students to online classes, (3) perception of the effects of coping mechanisms. Most participants applied three coping mechanisms, and these were (1) meditation and (2) spirituality which are considered adaptive coping mechanisms, and (3) late-night internet usage, a maladaptive coping mechanism. The participants expressed their vulnerability as a 1st-year student in terms of unfamiliarity due to the absence of face-to-face interaction, being unaccustomed to the new college environment, pressure due to unfamiliar teacher-student dynamic, and pressure in studying at a state university.